Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(i) (x + 3) (x + 7)
(x + 3) (x + 7) = x2 + (3 + 7)x + ( 3 x 7)
= x2 + 10x + 21
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x + 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x - 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2x +5y) (2x + 3y)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2a2 + 9) (2a2 + 5)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(xyz - 4) (xyz - 2)